Kinetic of denitrification and enhanced biological phosphorous removal (EBPR) of a trickling filter operated in a sequence-batch-reactor-mode (SBR-TF). Issue 17 (29th July 2021) - Cramer, Michael; Tränckner, Jens; Kotzbauer, Ulrich
ABSTRACT: Due to their limited ability for nutrient removal, trickling filter systems (TFS) have almost fallen into oblivion today, even though they are robust and energy-efficient treatment systems. The advantage of this process technology, however, is the sessile biomass, which allows long periods of starvation without rinsing out the biomass. Therefore, this technology is promising for treating organic-polluted, intermittent stormwater-runoff. Several combinations with activated sludge systems (ASS) use the trickling filter as pre-treatment, requiring two separate treatment systems. This combines the advantages of both systems, but is paid with increased investment costs and space requirement. Due to these concerns, a trickling filter was developed that allows a nutrient removal without an additional ASS and exemplary tested for treating stormwater runoff of a silo facility. Beside aerobic conditions, anoxic and anaerobic steps have to be ensured during the process for nutrient removal. For this, the TFS is ponded with a mix of purified wastewater from the secondary clarification tank (containing nitrate) and untreated raw water (containing degradable COD). This allows both, an integration of upstream-denitrification and enhanced-biological-phosphorous-removal (EBPR). During the anoxic step, nitrate removal rates of 0.8 kgCOD m −3 d −1 can be expected, whereas a maximum COD removal rate of 4.5 kgCOD m −3 d −1 are achieved. To support complete nitrification of ammonia, a COD removal rate below 0.5 kgCOD m −3 d −1 is recommended. The anaerobic/aerobic PO4 uptake rate of the EBPR was 31%. These results show that a combination of trickling filter with ASS in one single reactor is feasible. GRAPHICAL ABSTRACT: UF0001